Effect Of Employee Intelligence, Spiritual Intelligence And Adaptation Ability On Employee Engagement (Case Study On Non-Manager Employees At Taman Mangkubumi Indah Hotel, Tasikmalaya City) - Ossa Febriasari (Journal of Indonesian Management, 2022)
This study aims to determine and analyze the effect of emotional intelligence, spiritual intelligence and adaptability on employee engagement.. The method used in this research is causality through a case study approach. With a research sample of 40 non-manager employees at the Taman Mangkubumi Indah Hotel, Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that simultaneously Emotional Intelligence, Spiritual Intelligence and Adaptability had a significant effect on Employee Engagement. Partially Emotional Intelligence has a significant influence on Employee Engagement. Partially Spiritual Intelligence has a significant effect on Employee Engagement and Partially Adaptability Ability has a significant effect on Employee Engagement.